KEANEKARAGAMAN DAN KELIMPAHAN FILUM ECHINODERMATA PADA ZONA INTERTIDAL MOLAS KECAMATAN BUNAKEN KOTA MANADO - Novia A Jambo; Erly Y Kaligis; Deslie RH Kumampung; Suria Darwisito; Joshian NW Schaduw; Silvester B Pratasik (Sam Ratulangi University, 2021)
Echinoderms are one of the main components of marine biodiversity that play an important role in ecosystem function. The purpose of this study to determine the diversity, abudance,dominance, frequency and important value index of the phylum Echinoderm.The method use in this research was cruising method and the quadratic transect method. The results of this study on intertidal zone of Molas obtained as a whole includes four classes, namely Asteroidea, Echinoidea, Ophiuroidea and Holothuroidea with a total of 12 species. Based on data analysis used the quadratic transect method, it was obtained: at station I H' = 1.666, the highest species abundance index is Protoreaster nodosus at 1.133 ind/m2 and relative at 40.48%, C = 0.245 and the highest relative dominance of P. nodusus was 66.90%, the highest species frequency index is P. nodusus of 0.467 and a relative of 33.33% and the highest important value index is P. nodusus of 140.71% while at station II it is obtained H' = 1,384, The highest species abundance index is Diadema setosum at 3.067 ind/m2 and relative 55.42%, C = 0.359 and the highest relative dominance is D. setosum at 85.63%, the highest species frequency index is P. nodusus at 0.4 and relative at 27. 27% and the highest important value index of D. setosum was 159.23%.Keywords: Echinoderms, Diversity, Abundance, Dominance, Frequency, Important Value Index